2011
DOI: 10.1002/art.30333
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte AMP-activated protein kinase activity suppresses matrix degradation responses to proinflammatory cytokines interleukin-1β and tumor necrosis factor α

Abstract: Objective. Interleukin-1␤ (IL-1␤) and tumor necrosis factor ␣ (TNF␣) stimulate chondrocyte matrix catabolic responses, thereby compromising cartilage homeostasis in osteoarthritis (OA). AMP-activated protein kinase (AMPK), which regulates energy homeostasis and cellular metabolism, also exerts antiinflammatory effects in multiple tissues. This study was undertaken to test the hypothesis that AMPK activity limits chondrocyte matrix catabolic responses to IL-1␤ and TNF␣.Methods. Expression of AMPK subunits was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
173
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(191 citation statements)
references
References 47 publications
9
173
0
9
Order By: Relevance
“…In the present study, our data reveal that the OA-related catabolic factor IL-1β inhibits both activity of AMPK and ATP production in OA chondrocytes, suggesting that energy metabolism in chondrocytes is downregulated by OA-related factors during the progression of articular cartilage degeneration. Indeed, previous reports demonstrated that the activity of AMPK is decreased in chondrocytes in aged human and mouse OA cartilage [38,39]. Our findings of the downregulation of the AMPK ATP energy metabolic pathway in OA chondrocytes are consistent with their findings.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, our data reveal that the OA-related catabolic factor IL-1β inhibits both activity of AMPK and ATP production in OA chondrocytes, suggesting that energy metabolism in chondrocytes is downregulated by OA-related factors during the progression of articular cartilage degeneration. Indeed, previous reports demonstrated that the activity of AMPK is decreased in chondrocytes in aged human and mouse OA cartilage [38,39]. Our findings of the downregulation of the AMPK ATP energy metabolic pathway in OA chondrocytes are consistent with their findings.…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress, NF-kappaB activation, and iNOS induction are key mediators of these effects (Lo et al 1998;Grange et al 2006;Ahmad et al 2011;Pelletier et al 1998Pelletier et al , 1999. It is reasonable to suspect that AMPK might act to oppose these effects, and indeed, a recent study has found that AMPK activators notably suppress the catabolic response of chondrocytes to IL-1 or TNF-α exposure; notably, chondrocyte production of MMP-3, MMP-13, and NO was suppressed (Terkeltaub et al 2011). Conversely, knockout of AMPKa with small interfering RNA exacerbated the catabolic response of chondrocytes to IL-1 and TNF-α.…”
Section: Preserving Cartilage and Bonementioning
confidence: 99%
“…The altered response to TGF-β appears to occur at the receptor level due to changes in the ratio of ALK1 to ALK5 promoting more catabolic relative to anabolic activity [1,14], and for IGF-1, an altered balance of MAP kinase and Akt signaling due to ROS may be playing a role [15]. Other findings on OA chondrocytes that also might be linked to aging include reduced levels of Sirt1, a potential positive regulator of cartilage matrix gene expression [4,6], and a decline in AMPK activity, which could also promote a pro-catabolic state [13].…”
Section: Physiology Of Aging and Oamentioning
confidence: 99%